Thorium Fuel Cycle in BWR with Free 233U - Abdul Waris; W. Nawangsary; Syeilendra Pramuditya; Rizal Kurniadi (Institut Teknologi Bandung, 2007)
Study on thorium fuel cycle with free 233U in boiling water reactor (BWR) has been carried out. In this study we have utilized plutonium and minor actinides (MA) as fissile nuclides instead of 233U as one of the main scenario to obtain the 233U free BWR core with thorium. Beside that, the void-fraction of the reactor is modified from 20% up to 70%. The results show that the standard BWR core can maintain its criticality when the loaded fuel is thorium with 11.16% and 1.24 % of plutonium and MA, respectively. The use of 11.16% of Pu and 1.24 % of MA is more than enough to substitute the 1% of 233U to obtain thorium fuel cycle in the standard BWR with free 233U. Moreover, the lesser amount of plutonium and minor actinides in the fuel will results in the great degradation on the safety of reactor